Hard-Soft Real-Time Performance Evaluation of Linux RTAI Based Embedded Systems - Dodiu, E.; Graur, A.; Gaitan, V. G. (Elektronika ir Elektrotechnika, 2010)
A system is considered to be a hard real-time if all the computations are not only correct but their response is provided each time before a fixed deadline. Missing a deadline for such a system can possibly produce severe material damage or human health injury, therefore adequate testing and analysis should be done. This paper evaluates the suitability of a general purpose operating system like Linux with a real time extension. As it can be seen further on, Linux has overall good raw performance that can make it usable for an embedded system with industrial usage. To show the characteristics under full load stress, we have done several test cases for different scenarios that will be presented next in the paper.